2010
DOI: 10.19030/ajbe.v3i11.64
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration Of Differences Of Leadership Perceptions Related To A Student’s Gender Within The College Of Business At A Small Liberal Arts Institution

Abstract: <p class="MsoNormal" style="text-align: justify; line-height: normal; margin: 0in 0.5in 0pt; mso-pagination: none;"><em style="mso-bidi-font-style: normal;"><span style="font-family: &quot;Times New Roman&quot;,&quot;serif&quot;; font-size: 10pt;">In preparing the next generation of business professionals, educators need to take seriously the responsibility of empowering students with tools to assist them in their pursuits.<span style="mso-spacerun: yes;">&nbsp; <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Outside of higher education, emerging bodies of evidence exist regarding the differences between the leadership-oriented goals and actions between men and women (Eagly & Carli, 2003) and across different races and ethnicities (Bordas, 2007). Within the context of colleges and universities, research shows that differences exist by gender in student perceptions of capacity gains through leadership development programs (Yarrish, Zula, & Davis, 2010). Another study showed male students rated themselves higher than females, and Caucasian students higher than Students of Color, on a general measure of leadership ability (Kezar & Moriarty, 2000).…”
Section: Demographic Differences In Leadership Practicesmentioning
confidence: 99%
“…Outside of higher education, emerging bodies of evidence exist regarding the differences between the leadership-oriented goals and actions between men and women (Eagly & Carli, 2003) and across different races and ethnicities (Bordas, 2007). Within the context of colleges and universities, research shows that differences exist by gender in student perceptions of capacity gains through leadership development programs (Yarrish, Zula, & Davis, 2010). Another study showed male students rated themselves higher than females, and Caucasian students higher than Students of Color, on a general measure of leadership ability (Kezar & Moriarty, 2000).…”
Section: Demographic Differences In Leadership Practicesmentioning
confidence: 99%
“…Recently, universities and higher education institutions focused on developing students' leadership skills as a means of preparing them for the job market (Shertzer & Schuh, 2004;Yarrish, Zula, & Davis, 2010). This trend is motivated by the fact that leadership skills are not innate but acquired.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on leadership skills and self-perception of these skills has suggested that there are differences among both genders of their perceived skills (Burke & Collins, 2001;Eagly & Karau, 1991;Yarrish et al, 2010). A meta-analysis of the relationship between gender and leadership skills found that in groups without a leader, men emerged as leaders to a greater extent than women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to address the aim of this study, data were collected from 50 female students at the University of Dammam in Saudi Arabia and an analysis was conducted to see how these female students perceive leadership. As recently cited by Alexander (2011), universities and higher education institutions are increasingly focusing on developing students' leadership skills as a means of preparing them for the job market (Shertzer & Schuh, 2004;Yarrish, Zula & Davis, 2010). This trend was motivated by the fact that leadership skills are not innate but instead are acquired through education, training and mentorship (Fertman & Van Linden, 1999).…”
Section: Introductionmentioning
confidence: 99%